Managing media rich geo-spatial annotations for a map-based mobile application using clustering - RAZIKIN, Khasfariyati (Institutional Knowledge at Singapore Management University, 2010)
With the prevalence of mobile devices that are equipped with wireless Internet capabilities and Global Positioning System (GPS) functionality, the creation and access of user-generated content are extended to users on the go. Such content are tied to real world objects, in the form of geospatial annotations, and it is only natural that these annotations are visualized using a map-based approach. However, viewing maps that are filled with annotations could hinder the serendipitous discovery of data, especially on the small screens of mobile devices. This calls for a need to manage the annotations. In this paper, we introduce a mobile application, MobiTOP, which enable users to create multimedia geospatial annotations and employs a map-based visualization for users to explore the annotations. We propose the adoption of clustering approaches to manage the volume annotations on the map. Two approaches of clustering techniques, namely incremental clustering and DBScan (Density based spatial clustering applications with noise), are proposed and compared with a baseline approach in our evaluation. Implications of our findings are discussed.